صادق ثاجب علي تاثير مستويات مختلفه من الملوحة والحامضيه على بقاء يرقات بعوض الانوفلس - صادق ثاجب (University of Thi-Qar Journal of Science, 2019)
The effect of different levels of solutions salinity and acidity on the mortality of mosquitoes Anopheles sp. have been studied. The results showed that the mortality percentage was differed according to the solution concentrations, acidity level, and the exposure period. The highest mortality ratio was 98.39% at salt concentration of 20g/L after exposure period of 72 hours; For acidity level the highest mortality ratio was 97.27% at exposure period of 72 hours.